From Prosperity to Decline: The Transformation of the Bai Pala Ritual among the Dai People in Mangshi along the China-Myanmar Border from the Perspective of Religious Pluralism - Chen, Guirong; Yu, Yan’e (International Theory and Practice in Humanities and Social Sciences, 2025)
This study explores the mechanisms by which religious pluralism influences individual beliefs among the Dai people in Mangshi, with the transformation of the Bai Pala ritual as a case study. Data were collected through anthropological participant observation and semi-structured interviews. The findings reveal that since the 1940s, the Dai community in Mangshi has undergone profound transformations in social institutions, economic life, and cultural exchanges. The influx of diverse values during the modernization has exerted a significant "cognitive contamination" effect on the traditional beliefs of the Dai people, contributing to the decline of the once-prosperous Bai Pala ritual. The results show that while the "relativization" effect of religious pluralism has undermined the "certainty" of Theravada Buddhist beliefs at the cognitive level, individual religious participation exhibits salient differentiation. This suggests that the "plausibility structure" of Theravada Buddhism belief system possesses a degree of resilience, enabling its continuity in practice by adopting strategies including institutional attachment and functional adaptation, even when its cognitive certainty is compromised.